Using Mobile Augmented Reality to Increase Student English Language Learning - Julian Tri Hustanto; Punaji Setyosari; Henry Praherdhiono (JTP - Jurnal Teknologi Pendidikan, 2024)
This research explores the impact of mobile-assisted learning with augmented reality (AR) on beginner English language learners, focusing on the utilization of Internet of Things through QR codes. In the digital era, characterized by the dominance of the Alpha generation, mobile learning has become pivotal, aligning with student-centered approaches. The study addresses challenges in vocabulary learning, noting limitations in conventional methods and student motivation. The theoretical framework encompasses mobile-based learning, digital learning, and AR, emphasizing their role in transforming education. AR, with its elements like users, devices, interaction, virtual content, tracking, and real-life entities, is positioned as a powerful tool to enhance interactive learning experiences. The research aims to investigate how mobile-assisted learning with AR can overcome understanding barriers for English language learners and assess the feasibility of its design for beginners. Ultimately, the study suggests that the integration of digital technologies, especially AR, holds promise for revolutionizing English language learning, addressing vocabulary challenges, and catering to the learning preferences of the Alpha generation in the digital era.